Analisis Penentuan Harga Jual dengan Metode Cost Plus Pricing - Octavia, Devi Mega; Ervina, Deasy (JFAS : Journal of Finance and Accounting Studies, 2023)
The purpose of this study was to determine the calculation of the cost of production and the process of determine the selling price of fry at Jaya Samudra. This study calculates the cost of production using the full costing method and variable costing as well as determining the selling price using cost plus pricing. The type of research used is descriptive qualitative research. The data used in this study are primary data from interviews and information on Jaya Samudra’s production costs during 2021. The results of the analysis of research data show that the calculation of the company’s cost of goods manufactured is lower than the calculation using the full costing method, but when calculated by variable costing have in common. The determination of Jaya Samudra’s selling price is only carried out according to the market price. The selling price using the cost plus pricing method results in higher and lower resuluts, this happens when the price of the fry soars.